Predation on newly metamorphosed toad Rhinella ornata (Anura: Bufonidae) by the spider, Lycosa erythrognatha (Araneae: Lycosidae). - de Almeida, Silvio C.; Messas, Yuri F.; Cicchi, Paulo J.P. (My University, 2010)
Herein we report predation by the spider Lycosa erythrognatha on a newly metamorphosed anuran Rhinella ornata, observed in an aggregation of more than 50 individuals.